HEE-GER: a systematic review of German economic evaluations of health care published 1990-2004 - Schwappach David LB; Boluarte Till A (BMC, 2007)
Abstract Background Studies published in non-English languages are systematically missing in systematic reviews of growth and quality of economic evaluations of health care. The aims of this study were: to characterize German evaluations, published in English or German-language, in terms of various key parameters; to investigate methods to derive quality-of-life weights in cost-utility studies; and to examine changes in study characteristics over the years. Methods We conducted a country-specific systematic review of the German and English-language literature of German economic evaluations (assessment of or application to the German health care system) published 1990-2004. Generic and specialized health economic databases were searched. Two independent reviewers verified fulfillment of inclusion criteria and extracted study characteristics. Results The fulltexts of 730 articles were reviewed of which 283 fulfilled all entry criteria. 32% of included studies were published in German-language. 51% of studies evaluated pharmaceuticals and 63% were cost-effectiveness analyses. Economic appraisals concentrate on few disease categories and important health areas are strongly underrepresented. Declaration of sponsorship was associated with article language (49% English articles vs. 29% German articles, p < 0.001). The methodology used to obtain quality-of-life weights in published cost-utility studies was very diverse, poorly reported and most studies did not use German patients' or community health state valuations. Conclusion Many of the German-language evaluations included in our study are likely to be missing in international reviews and may be systematically different from English-language reviews from Germany. Lack of transparency and adherence to recommended reporting practices constitute a serious problem in German economic evaluations.